The Effect of Castration on Feedlot Performance and Non-Carcass Components of Young Male Sudanese Nubian Goats - Mohamed, Manal Yassin; Yagoub, Yagoub Magboul; Babiker, Salih Ahmed (Journal of agricultural, environmental and veterinary sciences, 2025)
This study was carried out to investigate the effect of castration on feedlot performance and non-carcass components of Sudanese Nubian Male Goats. Twenty Nubian Male Goats of similar weight (14.2 Kg) and similar age (less than a year) were used. Experimental Goats were divided into two groups of 10 goats each. The two groups took the same ration throughout the experimental period which lasted for 150 days. After the adaptation period, one group of goats was selected randomly for castration using the Burdizzo method, and the other group served as a control. Independent student t-test was used to examine the significance of differences between the two groups. Results showed that castration significantly (P< 0.01) reduced the final kid's weight.Live body weight gain and feed intake were insignificantly decreased. Non-carcass components were not significantly affected by castration except that mesenteric, omental, and kidney knob fat which were significantly (p
Keywords: Castration; Feedlot Performance; Non-Carcass Components; Male Sudanese Nubian Goats